Determinants Of Tax Aggressivity In Manufacturing Companies In The Consumption Goods Industry Sector Registered On The Idx - Putri, Helen Tiara; Noviardy, Andrian (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
Tax aggressiveness is an act of tax avoidance carried out by companies by carrying out tax planning (tax plaining) by exploiting loopholes in the law with the aim of reducing company profits so that tax savings can be implemented but carried out both legally and illegally, tax aggressiveness can be measured using the Effective Tax scale Rate (ETR) is the most commonly used in some literature. The range of ETR values that can identify tax aggressiveness or not. This research aims to determine the relationship between capital intensity, liquidity, profitability, leverage and company size on tax aggressiveness. The population in this study was manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (BEI) in 2019–2021. The sample selection method in this research was determined using a purposive sampling method which aims to obtain samples that comply with the specified criteria . The research results show that capital intensity has no effect on tax aggressiveness; the liquidity variable has no effect on tax aggressiveness; the profitability variable has a significant negative effect on tax aggressiveness; the leverage variable has no effect on tax aggressiveness; and the company size variable has no effect on tax aggressiveness.